Mechanizmy Finansowe 2004–2009 – pozaunijne źródła wsparcia rozwoju ekonomicznego i społecznego Polski - Guzowska, Aleksandra (Wydział Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2011)
The article deals with the financial instruments available in Poland as a result of being a part of the European Economic Area (EEA), i.e. the Norwegian Financial Mechanism and the EEA Financial Mechanism. The role and contribution of those Mechanisms to the socio-economical development of Poland are examined based on the financial perspective 2004-2009. Firstly, the author presents the organizational and legal framework, the general principles, the rules for distributing sources as well as the components that enabled use of funds coming from those instruments on the Polish ground, such as: the management and implementation system along with the institutional system. This background enables the review of all priority areas and funds, presenting their particular aims and assumptions. Bearing in mind a closing stage of the financial perspective 2004-2009 the author shows the level of achieved indicators and some examples of carried out undertakings. The article tries to present the assessment of first effects of projects’ implementation as well as the most important lessons learned with the way of taking them into consideration in the next financial perspective of the Norwegian Financial Mechanism and the EEA Financial Mechanism 2009-2014.
Summary Financial Mechanisms 2004-2009? Non-EU sources of support for Poland’s economic and social development